Solar‐Blind Ultrathin Sn‐Doped Polycrystalline Ga2O3 UV Phototransistor for Normally Off Operation. Issue 5 (3rd May 2022) - Yoon, Youngbin; Hwang, Wan Sik; Shin, Myunghun
Abstract : Phototransistors The fully depleted 8‐nm‐thick polycrystalline β ‐Ga2 O3 semiconductor with wafer‐scale substrate expedites the realization of high‐performance, low‐power‐consumption solar‐blind photodetectors. The extremely low thickness of Ga2 O3 causes a quantum confinement effect and allows the proposed device to successfully achieve detection in the deep UV region (215 nm). More information can be found in article number 2100316 by Myunghun Shin and co‐workers.